(untitled) (Revista Lusófona de Educação, 2020)
It is clear that language-friendly and language-skilled higher education institutions are essential if an internationalisation is to be achieved which promotes the well-being of the academic community as a whole and the inclusion and success of all students. However, this premise poses many challenges for institutions, particularly those which are not located in the mainstream of the Anglophone higher education sphere. In such contexts, an internationalisation strategy which relies on the adoption of English as the medium of instruction and research is not sufficient to meet local and international demands. Adding to a growing body of research carried out in a wide range of higher education contexts, this article explores the importance attributed to internationalisation and language strategies by the University of Aveiro in its institutional policy documents in the period 2010 – 2018. It finds that languages are an important consideration in the institution’s internationalisation strategy which seeks a balance between two linguas francas, Portuguese and English, and recognises the contribution of languages to institutional life and graduate profiles. Keywords: higher education institutions; internationalisation; globalisation; language policy; inclusion and well-being.